Preschool Education in the Light of Current Program Assumptions. Selected Aspects - Ordon, Urszula (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
In the context of current education reforms carried out at various levels of education, it is important to ask about high quality and child friendly preschool education. As stated by Klim-Klimaszewska, “preschool education in Poland is the first stage of education system. Its main task is not only to help parents in mentoring and education of children, but first of all to stimulate their comprehensive development and school preparation” (Klim-Klimaszewska, 2012, p. 9). At the level of preschool education we observed multidimensional transformations that aimed at new approach to the theory and paradigms of education, which serves improvement of effectiveness of children’s education.
Keywords: child; preschool education; core curriculum; program changes; directions of transformation